2022
DOI: 10.1002/ccr3.5505
|View full text |Cite
|
Sign up to set email alerts
|

Twisting of the Ranger drug‐coated balloon for treating superficial femoral artery disease

Abstract: Paclitaxel‐coated balloons have demonstrated improved efficacy compared with uncoated percutaneous transluminal angioplasty for femoropopliteal artery disease. While applying a long balloon, twisting of the balloon can be occurred. We reported two cases with twisting of the Ranger drug‐coated balloon for treating superficial femoral artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Esses estudos são essenciais para estabelecer relações causais e fornecer recomendações baseadas em evidências (Zhao & Wang, 2019). Os relatos de caso, embora menos frequentes, são fundamentais para identificar e documentar eventos raros ou efeitos adversos não previstos, que podem não ser evidentes em estudos maiores (Kim & Choi, 2022). Os estudos pré-clínicos, como ressaltado por Anderson e Thompson (2020), desempenham um papel vital na compreensão inicial dos mecanismos de ação do Orlistate e seus potenciais efeitos colaterais, fornecendo uma base para ensaios clínicos subsequentes.…”
Section: Discussõesunclassified
“…Esses estudos são essenciais para estabelecer relações causais e fornecer recomendações baseadas em evidências (Zhao & Wang, 2019). Os relatos de caso, embora menos frequentes, são fundamentais para identificar e documentar eventos raros ou efeitos adversos não previstos, que podem não ser evidentes em estudos maiores (Kim & Choi, 2022). Os estudos pré-clínicos, como ressaltado por Anderson e Thompson (2020), desempenham um papel vital na compreensão inicial dos mecanismos de ação do Orlistate e seus potenciais efeitos colaterais, fornecendo uma base para ensaios clínicos subsequentes.…”
Section: Discussõesunclassified
“…In a recent article, SH Kim et al [7] have reported the use of DCB for treating superficial femoral artery. They have found cases of twisting of the Ranger paclitaxel-coated PTA balloon catheter in the case of two 73-year-old men with history of hypertension and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%